Novel serum paraoxonase activity assays are associated with coronary artery disease - Martinelli, Nicola; Girelli, Domenico; Olivieri, Oliviero; Guarini, Patrizia; Bassi, Antonella; Trabetti, Elisabetta; Friso, Simonetta; Pizzolo, Francesca; Bozzini, Claudia; Tenuti, Ilaria; Annarumma, Laura; Schiavon, Renzo; et al. (Clinical chemistry and laboratory medicine, 2009)
Background: Serum paraoxonase (PON1) exerts antiatherogenic effects. Novel PON1 enzymatic tests have been recently developed: 5-thiobutyl butyrolactone (TBBL) estimates PON1 lactonase activity, whereas 7-O-diethylphosphoryl-3-cyano-4-methyl-7-hydroxycoumarin (DEPCyMC) is considered a surrogate marker of PON1 concentration. The TBBL to DEPCyMC ratio provides the normalized lactonase activity (NLA), which may reflect the degree of PON1 lactonase catalytic stimulation. The aim of this study was to evaluate for the first time TBBLase and DEPCyMCase activity in patients with coronary artery disease (CAD). Methods: An angiography-based case-control study was conducted, including 300 sex- and age-matched subjects [100 CAD-free, 100 CAD without myocardial infarction (MI) and 100 CAD with MI]. Results: A low DEPCyMCase activity (lowest vs. highest tertile: OR 2.96, 95% CI 1.18–7.43) and a high NLA (highest vs. lowest tertile: OR 3.25, 95% CI 1.28–8.26) were both associated with CAD, independent of classical atherosclerosis risk factors, lipid-lowering therapy and PON1 genotype. Total TBBLase activity was, however, not different in CAD compared to CAD-free subjects. Conclusions: Novel PON1 activity assays may be associated with CAD. In this study, CAD patients had low DEPCyMCase activity, a possible marker of low PON1 concentration, but showed a high stimulation of PON1 lactonase activity. Clin Chem Lab Med 2009;47:432–40.